Additive manufacturing of continuous carbon fiber reinforced epoxy composite with graphene enhanced interlayer bond toward ultra‐high mechanical properties. Issue 2 (1st December 2021) - Parandoush, Pedram; Li, Xuemu; Chang, Baoning; Sorensen, Christopher M.; Shi, Jing; Liu, Yuan; Lin, Dong
Abstract: Continuous carbon fiber reinforced polymer composites (CFRPCs) exhibiting superior mechanical properties have emerged as high‐performance engineering materials for various industrial applications. Additive manufacturing (AM) of CFRPCs enables production of customized structures with superior mechanical properties at a low cost and has gained tremendous popularity. In the present study, a novel AM technique namely laser‐assisted laminated object manufacturing (LA‐LOM) is proposed for producing CFRPCs using prepreg sheets with continuous carbon fiber reinforcement. The interfacial properties of the bonded prepreg sheets are critical for the performance of the additively manufactured CFRPCs. We further introduce graphene as a modifier between the prepreg sheets to improve the mechanical properties of the CFRPCs. It is shown that low porosity (0.38%), high concentrations of continuous carbon fibers (63 wt. %), and improved interfacial bonding strength contribute to excellent mechanical properties. For the composite structure ([0°]s fiber arrangements), in which 0.5 mg/ml graphene is introduced as interface modifier, the lap shear strength, tensile strength, and tensile modulus are 18 MPa, 2940 MPa, and 170 GPa, respectively, and the flexural strength and modulus are 1310 MPa and 140 GPa, respectively. The tensile strength and modulus outperform all AM‐produced structures reported in literature, including carbon fiber composites and metals and metal alloys. Meanwhile, the increases are observed in the lap shear strength by 25%, flexural strength by 10%, and flexural modulus by 27%, as well as tensile strength by 7% and modulus by 6%, compared to specimens without graphene reinforcement. This composite architecture design, involving laminated continuous carbon fiber reinforced prepreg sheets and graphene‐modified interfaces, provides a readily scalable manufacturing method toward excellent properties and this method can be further explored in industrial applications. Abstract : Additively manufactured carbon fiber composites via laser‐assisted laminated object manufacturing are enhanced by adding graphene to the composite interface to improve inter‐layer bonding and overall mechanical properties. Void content is only 0.38% and mechanical properties are improved compared to composites with no graphene additives.